2012
DOI: 10.1093/humupd/dms050
|View full text |Cite
|
Sign up to set email alerts
|

BMI in relation to sperm count: an updated systematic review and collaborative meta-analysis

Abstract: BACKGROUND The global obesity epidemic has paralleled a decrease in semen quality. Yet, the association between obesity and sperm parameters remains controversial. The purpose of this report was to update the evidence on the association between BMI and sperm count through a systematic review with meta-analysis. METHODS A systematic review of available literature (with no language restriction) was performed to investigate the impact of BMI on sperm count. Relevant studies published until June 2012 were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
344
6
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(404 citation statements)
references
References 73 publications
(129 reference statements)
13
344
6
11
Order By: Relevance
“…Several studies have reported on the impact of BMI on semen parameters, resulting in two recent meta-analyses (MacDonald et al, 2010;Sermondade et al, 2013). Unexpectedly, sperm concentration was not impaired in general, although morbidly obese men (BMI ≥40) were more likely to have oligozoospermia or azoospermia (MacDonald et al, 2010;Sermondade et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the impact of BMI on semen parameters, resulting in two recent meta-analyses (MacDonald et al, 2010;Sermondade et al, 2013). Unexpectedly, sperm concentration was not impaired in general, although morbidly obese men (BMI ≥40) were more likely to have oligozoospermia or azoospermia (MacDonald et al, 2010;Sermondade et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only a limited number of studies evaluated seminal tract inflammation in patients with elevated body mass index (BMI) (Lotti et al, 2011;Tunc et al, 2011;Thomas et al, 2013). Two recent meta-analyses assessed a potential association of body weight and sperm quality, one of which revealed no negative effects (MacDonald et al, 2010), while the other reported a twofold increase in the prevalence of azoospermia or oligozoospermia in patients BMI greater 40 (Sermondade et al, 2013). In terms of MetS, however, data on sperm parameters are both scarce and controversial (Robeva et al, 2008;Lotti et al, 2013Lotti et al, , 2014Leisegang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Jensen et al [108] studied over 1558 younger men having paramilitary physical and found that overweight men had reduced sperm concentration as compared with normal weight. The effect of BMI on sperm parameters has been apparently investigated in several scientific studies which document that prevalence of azoospermia or oligozoospermia were associated with an increased overweight and obesity [109]. Our previous investigation about BMI and sperm function also clarify that sperm function with sperm concentration, motility and vitality shows a significant and negative relationship with body mass index (BMI); In contradictory to Thomsen et al [110] investigation, our results shows a significant declination in sperm concentration, motility and vitality in overweight and obese male as compared to normal male.…”
Section: Life Stylementioning
confidence: 99%
“…Whether the opposing syndrome, loss of adipose tissue, or lipodystrophy impacts on male infertility remains largely unexplored. A single metaanalysis evaluating body mass index and male semen quality reported that underweight was associated with an increased but nonsignificant risk of abnormal sperm count (5). A study on several types of lipoatrophies mentioned that men with congenital generalized lipodystrophy (CGL) were fertile, but it did not present specific data (6).…”
mentioning
confidence: 99%